Integrative taxonomy reveals Pseudokeissleriella tetradii sp. nov. (Lentitheciaceae, Pleosporales) associated with Tetradium ruticarpum in Anhui Province, China - Mi, Li-Xue; Song, Hai-Yan; Eungwanichayapant, Prapassorn D.; Hu, Dian-Ming (Phytotaxa, 2025)
Tetradium ruticarpum, a well-known medicinal plant in China, is widely used in traditional medicine to treat pain and gastrointestinal disorders due to its diverse bioactive components. During a fungal survey of T. ruticarpum in Anhui Province, China, a novel coelomycetous species, Pseudokeissleriella tetradii was isolated and characterized. The new species is morphologically distinguished by dark brown to black, globose conidiomata; cylindrical, aseptate conidiophores; holoblastic conidiogenous cells; and hyaline, aseptate, cylindrical to subcylindrical, guttulate conidia. Phylogenetic analyses based on a combined SSU, ITS, LSU, and tef1-α sequences, placed the taxon within Pseudokeissleriella as a sister species to the bamboo-inhabiting Ps. bambusicola (SH-aLRT/UFBoot/BPP = 95.7/96/1.0). Distinct morphological traits and interspecific genetic differences support its recognition as a new species. The discovery expands the known host range of Pseudokeissleriella beyond bamboo and highlights the unexplored fungal associate with medicinal plants. A detailed description, illustrations, phylogenetic analysis results, and genetic comparisons are provided.